ANALISIS POTENSI EKONOMI SEKTOR/SUB SEKTOR PERTANIAN PROVINSI BENGKULU - Saputra, Rahmat Bayu; Sukiyono, Ketut; Nabiu, Musriyadi (AGRITROPICA : Journal of Agricultural Sciences, 2025)
The Gross Regional Domestic Product (GRDP) of Musi Rawas Regency continues to increase significantly. One of the sectors contributing the second-largest share is agriculture, forestry, and fisheries. This sector accounts for 29.42% of Musi Rawas Regency's total GRDP. It includes food crop agriculture, horticulture, plantation crops, livestock, and agricultural and animal hunting services for commercial purposes. In 2021, the area of oil palm plantations in Musi Rawas Regency was 38,542.10 hectares, with a production of 106,339.69 quintals of palm oil. The purpose of this research is to analyze the leading commodities, identify internal and external factors influencing their development, and develop strategies to advance their development in the Musi Rawas Regency. The research respondents include academics and practitioners, and the study uses both primary and secondary data. The data analysis methods employed are the Analytic Hierarchy Process (AHP) and SWOT analysis. The results of the Analytic Hierarchy Process analysis indicate that the leading plantation commodity in Musi Rawas Regency is oil palm cultivation (0.377), followed by rubber plantations (0.213), coconut (0.136), coffee (0.134), cocoa (0.098), and sugarcane (0.042). The priority strategy for developing the Leading commodity of oil palm plantations in Musi Rawas Regency is to improve supporting facilities and infrastructure.